2013
DOI: 10.1073/pnas.1308768111
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical basis for the inhibition of cell death by APIP, a methionine salvage enzyme

Abstract: APIP, Apaf-1 interacting protein, has been known to inhibit two main types of programmed cell death, apoptosis and pyroptosis, and was recently found to be associated with cancers and inflammatory diseases. Distinct from its inhibitory role in cell death, APIP was also shown to act as a 5-methylthioribulose-1-phosphate dehydratase, or MtnB, in the methionine salvage pathway. Here we report the structural and enzymatic characterization of human APIP as an MtnB enzyme with a K m of 9.32 μM and a V max of 1.39 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…It has also close counterparts in eukaryotes (Pirkov et al, 2008). Gene APIP, for example, is the counterpart in H. sapiens where it is involved in the control of the key process of apoptosis (Kang et al, 2014a). Two different types of reactions have been recruited to generate 1,2-dihydroxy-3-keto-5methylthiopentene.…”
Section: Blue Arrows)mentioning
confidence: 99%
“…It has also close counterparts in eukaryotes (Pirkov et al, 2008). Gene APIP, for example, is the counterpart in H. sapiens where it is involved in the control of the key process of apoptosis (Kang et al, 2014a). Two different types of reactions have been recruited to generate 1,2-dihydroxy-3-keto-5methylthiopentene.…”
Section: Blue Arrows)mentioning
confidence: 99%
“…A recent report showed that APIP exists as a tetrameric complex which is essential for the methionine salvage pathway [32]. In gastric cancer, APIP also forms a tetrameric complex and the inhibition of APIP/APIP interactions blocks its oncogenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…APIP encodes the APAF1-interacting protein, which has methylthioribulose 1-phosphate dehydratase activity and is involved in the methionine salvage pathway (28). APIP deficiency is associated with cell death and cancer (29,30).…”
Section: Discussionmentioning
confidence: 99%